Hybrid flexible arc suppression device based on soft grid connection strategy for MV distribution systems. Issue 17 (22nd April 2021) - Zheng, Ze‐Yin; Guo, Mou‐Fa; Jin, Tao; Liu, Jian‐Hong
Abstract: As an essential apparatus in resonance grounding systems, the arc suppression coil is widely used in rejecting the single‐line‐to‐ground (SLG) fault of distribution networks. However, the resistive ground‐fault current cannot be compensated by an arc suppression coil (ASC). As a novel active arc suppression device, the hybrid flexible arc suppression device (HFASD) composed of ASC and flexible arc suppression device (FASD) can eliminate the capacitive component of ground‐fault current and the resistive component of ground‐fault current. After the SLG fault occurs, the FASD from stand‐alone mode to grid‐connected mode may lead to switching transients, affecting the stability of distribution networks. The soft grid connection (SGC) strategy can achieve low or without transient response during the grid synchronization of FASD to the grid. Thus, the HFASD based on SGC strategy and segmented proportional‐integral‐differential (SPID) and second‐order generalized integrator phase‐locked loop (SOGI‐PLL) control method is proposed for rejecting the current and voltage overshoot responses during the process of grid synchronization of FASD in this paper. Simulation and experimental results verify the effectiveness of the proposed method, and the benefit of the proposed method is indicated in comparison with the non‐SGC (NSGC) strategy.